2019
DOI: 10.1177/0300060519888102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common causes of neuropathic pain in Korea: population-based observational study

Abstract: Objective: To investigate the prevalence of complex regional pain syndrome (CRPS), postherpetic neuralgia (PHN), trigeminal neuralgia (TN), and diabetic neuropathy (DN), common causes of neuropathic pain encountered in pain clinics. Methods: We investigated the period prevalence rate of CRPS, PHN, TN, and DN using data from a Korean national electronic database from 2009 to 2013. Results: The prevalence of CRPS decreased slightly throughout the study period, while the prevalence of PHN increased from 2009 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In Korea, one study previously mentioned that the prevalence of TN was 81.8 per 100,000 person-years [ 21 ]. However, there was no consideration of the various epidemiological characteristics of TN in that study.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, one study previously mentioned that the prevalence of TN was 81.8 per 100,000 person-years [ 21 ]. However, there was no consideration of the various epidemiological characteristics of TN in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain has demonstrated significant sex-based differences in many studies. The prevalence of neuropathic pain, such as TN, postherpetic neuralgia (PHN), complex regional pain syndrome (CRPS), and fibromyalgia, was shown to be higher in women compared with in men [ 112 , 113 , 114 ]. Coyle et al used partial sciatic nerve ligation to establish neuropathic pain in rats and found that a larger proportion of female rats developed tactile allodynia [ 115 ].…”
Section: Potential Sex-based Differencesmentioning
confidence: 99%
“… 34 The standardized prevalence of PHN increased annually from 1.6/1,000 persons in 2009 to 2.2/1,000 persons in 2013 in Korea. 95 …”
Section: Resultsmentioning
confidence: 99%